Analisis Dan Perancangan Sistem Penunjang Keputusan Menentukan Guru Berprestasi Di Smk Pelita Raya Jambi Dengan Metode Simple Additive Weighting - Gulo, Trisnawati; Roestam, Rusdianto (Jurnal Manajemen Sistem Informasi, 2020)
In improving performance and reward for teachers, management of SMK Pelita Raya implement a systemof teacher assessment to determine teacher achievers every one year teaching based on five criteria that isdisciplined, loyalty, completeness of teaching, effective teaching hours, and attitude. Based on fiveassessment criteria teacher achievers, top level management of SMK Pelita Raya getting the end resultthat is subjective because the top level management are not quite satisfied with the quality of theinformation obtained. To get the end result that objective, it is necessary a new system i.e. systemsupporting decisions by using Simple Additive Weight or weighted summation methods as well as theassessment criteria of group penamahan more precise. Concept of a Simple Additive method Weight(SAW) is seeking a weighted summation of rating the performance of each alternative on all attributes.Thus this decision support system is expected to present the results of the right information to supportdecision making.